BIMFlexi-VR: A Virtual Reality Framework for Early-Stage Collaboration in Flexible Industrial Building Design - Podkosova, Iana; Reisinger, Julia; Kaufmann, Hannes; Kovacic, Iva (Frontiers in Virtual Reality, 2022)
Integrated industrial building design is an interdisciplinary task, in which planning of flexible building structures requires effective communication and collaboration between all stakeholders already in early design stage. This paper presents BIMFlexi-VR, a collaborative framework which implements a real-time bidirectional link between a parametric modelling component created in Grasshopper for Rhinoceros that performs optimized structural calculations of an industrial building, and an immersive Virtual Reality environment in which the automatically calculated building is visualized. Users of BIMFlexi-VR are able to change parameters defining the outcome of the structural calculation directly inside the virtual environment and see the modified building design together with the associated fitness metrics in a matter of seconds. Providing an efficient and intuitive platform for early exploration of industrial building designs, BIMFlexi-VR enables collaborative decision making and facilitates the creation of more efficient and sustainable industrial constructions.